THE DUAL PURPOSE OF TEACHING LITERATURE: TO PROVIDE STIMULATING COURSE CONTENT AND TO DEVELOP STUDENTS’ COMMUNICATIVE ABILITIES - Budiati Budiati (JURNAL SOSIAL HUMANIORA (JSH), 2013)
It is the individual reader’s freedom to interpret a text according to his own outlook on the world that makes the study of literature such an exciting and liberating experience. This paper will look at some of the issues and ways in which literature can be exploited in the classroom and focus on the use of short stories as alternative materials that can encourage learners in a variety of classroom activities: from vocabulary enrichment to communicative abilities. Categories that encourage learners to develop the powers to interpret the texts are plot and suspense; characters and relationships; major themes; methods writer uses to communicate his attitudes; and reader’s response. Short stories can also lend themselves to intercultural values comparisons. Finally, it is expected that this paper can offer insights to other language teachers who are in similar settings.